Identities of Phuan Language and Hom Culture of Thung Hong Village, Phrae Province - Rattanawong, Nopparat (Journal of Graduate MCU KhonKaen Campus, 2023)
This article aims to present the relationship between Thung Hong (Thai-Puan) language and Hom culture maintenance of Thung Hong village, regarded as the Thai-Phuan community of Phrae province. Language is one of the most significant markers of ethnic identification and it plays a crucial role not only in the external perception of an ethnic group by outsiders but also in the self-identification of an ethnic group. It symbolizes identities and it is used to signal identities by those who speak them. Northern Thai dialects and cultures are important since they are the sources of knowledge, culture, traditions, and local wisdom. More details of Hom culture and are presented in the introduction and passages below to show how Thung Hong (Thai-Phuan) language is related and linked in harmony with it.